2021
DOI: 10.1038/s41419-020-03375-z
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Mas receptor mediates lipid-induced kidney injury

Abstract: Obesity-related kidney diseases are becoming serious health problems worldwide, yet the mechanism by which obesity causes kidney injury is not fully understood. The purpose of current study was to investigate the role of Mas receptor in lipid-induced kidney injury. In mice fed with high-fat diet (HFD), the protein abundance of markers of autophagy, endoplasmic reticulum stress (ER stress) and apoptosis was dramatically increased in the kidney cortex, which was markedly prevented by Mas deletion (Mas−/−) or Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…To investigate whether this could be occurring in our cEV treated normal cells, we treated HPDE-H6c7 ERSE luciferase reporter cells with various concentrations of palmitic acid. We found that ER stress was induced at 75 μM (Figure 7c), well below commonly reported doses of 250-500 μM and higher in other cell types (Ben-Dror & Birk, 2019; Kong et al, 2021). We confirmed upregulation of DDIT3 protein 24 h after treatment with 75 μM of palmitic acid (Figure 7d).…”
Section:  Proteomics Lipidomics and Metabolomics Studies Reveal Enr...supporting
confidence: 77%
“…To investigate whether this could be occurring in our cEV treated normal cells, we treated HPDE-H6c7 ERSE luciferase reporter cells with various concentrations of palmitic acid. We found that ER stress was induced at 75 μM (Figure 7c), well below commonly reported doses of 250-500 μM and higher in other cell types (Ben-Dror & Birk, 2019; Kong et al, 2021). We confirmed upregulation of DDIT3 protein 24 h after treatment with 75 μM of palmitic acid (Figure 7d).…”
Section:  Proteomics Lipidomics and Metabolomics Studies Reveal Enr...supporting
confidence: 77%
“…We found that ER stress was induced at 75 µM (Fig. 6c), well below commonly reported doses of 250 µM -500 µM and higher in other cell types 44,45 . This suggests that enrichment of palmitic acid in cEVs may induce ER stress in part, leading to activation of the UPR in treated normal cells.…”
Section: Proteomics Lipidomics and Metabolomics Studies Reveal Enrichment Of Potential Upr/er Stress Mediators In Cevssupporting
confidence: 55%
“…In contrast to the studies that suggest a protective role for the ACE2/Ang-(1-7)/Mas receptor axis, accumulating evidence suggests that downregulation of this pathway may be beneficial in disease settings. For example, genetic and pharmacological Mas receptor deficiency has been reported to prevent high-fat diet–induced kidney injury ( Kong et al, 2021 ), abolish salt-sensitive hypertension ( Heringer-Walther et al, 2012 ), reduce kidney damage in models of kidney injury (e.g., unilateral ureteral obstruction and ischemia/reperfusion injury) ( Esteban et al, 2009 ), and inhibit NF- κ B activation and thus the upregulation of proinflammatory cytokines ( Esteban et al, 2009 ). Clearly, more studies are needed to establish the contribution of the ACE2/Ang-(1-7)/Mas receptor axis in kidney health and disease, also in view of the fact that recent studies do not support that Ang-(1-7) is the endogenous agonist of the Mas receptor ( Gaidarov et al, 2018 ).…”
Section: Receptors Involved In the Effects Of Kidney Angiotensinsmentioning
confidence: 99%